Establishment of research methods and protocols in cytogenetic laboratory of the Kulliyah of Medicine, IIUM - Muhammad, Siti Aeshah @ Naznin (IIUM Press, 2009)
Cytogenetic is the study of chromosomes at the cellular level. Only cells that are actively dividing can be used for cytogenetic studies. Although specific techniques differ according to the types of tissue culture, addition of a mitotic inhibitor to arrest cells at metaphase, harvesting of cells, slide preparation and staining of the chromosomes. Since every cytogenetic laboratory has a different method of culturing samples, the aim of this study is to establish the method of lymphocyte and bone marrow cultures in our newly established cytogenetic laboratory of Kulliyyah of Medicine IIUM. Samples of peripheral blood and bone marrow were cultured using different culture techniques. Variations for each technique were instituted for the purpose of optimization. Different protocol for harvesting, slide making and banding were carried out to maximize the yield that is to obtain good quality of chromosomes for analysis. Fifty peripheral blood and 400 bone marrow aspiration cultures were set up. In the initial stages the yield of the cultures were poor. Some of the cultures were infected, mainly due to the prolonged incubation period. The harvesting technique was generally satisfactory though intermittently cytoplasmic problem and cell clumps were encountered. The banding methods used were Giemsa and Leishman banding. Generally for bone marrow cultures in addition to poor banding quality, the number of metaphase spreads obtained was poor and inadequate for analysis. Though the result obtained it was found that it has improved markedly, several stages of the methods need to be further optimized in order to obtain good number of metaphase spreads and also to improve the banding quality which will make it possible to analyze the chromosomes.